Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1353/hpu.2010.0551
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Centers: Unrecognized Partners in Health Professions Education

Abstract: Increasing demand for health professionals with training in ambulatory and primary care practice is placing stress on existing training site capacity. Community health centers can serve as model training sites, offering comprehensive multidisciplinary health care services and teaching clinician role models. In this study, 32 Illinois community and migrant health centers and federally qualified health centers were surveyed to assess their involvement with training in the past three years. Thirty centers had off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7][28][29][30] CHC-FMR affi liations offer one possible solution to this workforce shortage through enhanced teaching and recruitment of residents to underserved areas, [33][34][35][36][37][38][39][40]44 This study provides a description of the factors that determine a successful affi liation between CHCs and FMRs, and adds to the call for adoption of policies to pave the way for more successful partnerships. 6,16,17,23,32,[48][49][50][51] We found 4 themes that describe the facilitators of and barriers to CHC-FMR affi liations: (1) mission, (2) money, (3) governing institutional barriers and administrative challenges, and (4) quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][28][29][30] CHC-FMR affi liations offer one possible solution to this workforce shortage through enhanced teaching and recruitment of residents to underserved areas, [33][34][35][36][37][38][39][40]44 This study provides a description of the factors that determine a successful affi liation between CHCs and FMRs, and adds to the call for adoption of policies to pave the way for more successful partnerships. 6,16,17,23,32,[48][49][50][51] We found 4 themes that describe the facilitators of and barriers to CHC-FMR affi liations: (1) mission, (2) money, (3) governing institutional barriers and administrative challenges, and (4) quality.…”
Section: Discussionmentioning
confidence: 99%
“…Such affi liations have existed for more than 20 years; they provide effective training and increase the number of graduates working in safety net health care settings. [33][34][35][36][37][38] Graduates of these programs are 4 times more likely than graduates from nonaffi liated programs to continue to work in CHCs. A recent analysis from the WWAMI (Washington, Wyoming, Alaska, Montana, Idaho) Family Medicine Residency Network showed that 80% of graduates from residency programs affi liated with CHCs worked in underserved areas in the year after graduation.…”
Section: R Esident S In Co Mmunit Y He Alt H Cent Er Smentioning
confidence: 99%
See 2 more Smart Citations
“…Communityacademic partnerships have the potential to improve the health of the community, further the service missions of schools, and often provide educational opportunities for both learners and community clinicians. [35][36][37][38][39] The case study by Kaufman and colleagues 40 at the University of New Mexico conveys the enormous potential of effective academic-community partnerships for improving the care of the uninsured while cutting avoidable costs. Like many AHCs, the University of New Mexico has been the major source of care for a large uninsured population spread over a large geographic area.…”
Section: Indigent Carementioning
confidence: 99%